PUBLIC SERVICE ADVERTISING: AN ANALYSIS ON TEXT AND SEMIOTICS - Sukarini, Ni Wayan (e-Journal of Linguistics; Vol. 6. Juli 2012 No. 2, 2012)
This study concerns with text and semiotics analysis on the use of language in public service advertising (PSA). PSA in this study is the text which is especially on health. There are three problems that are analysed in this research, namely: (1) grammatical structure and the lexical of the text; (2) the relationship of trichotomies (representamen, object, and interpretant) with the three components of sign in nonverbal aspect; and (3) ideologies and messages conveyed in the verbal and nonverbal signs. Three methods applied in this research respectively including descriptive, qualitative, and interpretative. The type of data was the written one which was taken from printed media in the forms of poster and brochure. The data was collected through five procedures, they are clipping, numbering, coding, picturing, and documenting. As a scientific writing, a number of theories must be applied for the analysis. The relevant theories are semantics, semiotics, speech act, hermeneutics, language function, and text structure. These six theories were applied eclecticly in analysing the grammatical structure, lexicals, signs, and the structure of texts in order to elaborate the meaning, ideology, and message which were being conveyed through the texts of PSA. The result of the analysis showed that the grammatical structure applied in the PSA of health could be classified into the simple structure in the forms of phrase, clause, and sentence. The use of verbs dominated initially in order to express the imperative meaning but still had the purpose of being persuasive. Kinds of lexicals found were very close to disease, reproduction, and health either the general terms, for example victims, medicine or the specific ones like HIV/AIDS, Odha, perinatal, nifas, jampersal, sadari. From the nonverbal aspect, the relationship of trichotomy with the three of sign components are more realistics in the Object with its three sub components. Triadic relationship of three sub components of Object show close relationship and generally each of the component is not exclusive. All of those three gave influence since a sign is formed through those three sub components. The general and main ideology is the culture of being healthy with its variaties which have something to do with cleanliness, health, consciousness, awareness, alertness, togetherness, planning, welfare, and happiness.The messages conveyed through ideologies are proceeded to the target audiences to begin a well prepared life followed by paying good attention and care to themselves and the environment in order to gain health, welfare, and peace.
Keywords: verbal nonverbal, meaning, ideology, message.